Fiqh Al-Hadis Review on Children Status as Result of Premarital Intercourse - Muhammad Miftah Alkausar; Ananda Prayogi (Qur'an and Hadith Academic Society, 2023)
Premarital intercourse is not only an issue in society but also a serious discussion in religion. The outcome is the birth of a child whose lineage becomes a questionable. This article aims to answer this issue from the perspective of Islamic law with the Fiqh al-Hadis approach. The research employs a library research method with an approach of Fiqh al-Hadis to analyze narrations and significancy of the hadith by collecting all the related history, examining the validity and quality of the hadith and explaining how mazhab scholars argue about the meaning and purpose of discussed hadith text. Eventually, it is found that among mazhab scholars, there are agreements and differences in understanding the text and substantive of the ‘lil firasy’ hadith. From the various results of reasoning, mazhab scholars can provide clear stipulations in determining lineage status and can also be a way out for the community in this case.